Afatinib as first-line treatment in patients with EGFR-mutated non-small cell lung cancer in routine clinical practice. (May 2021) - Brückl, Wolfgang M.; Reck, Martin; Griesinger, Frank; Schäfer, Harald; Kortsik, Cornelius; Gaska, Tobias; Rawluk, Justyna; Krüger, Stefan; Kokowski, Konrad; Budweiser, Stephan; Ficker, Joachim H.; Hoffmann, Christopher; et al.
Background: Lung cancer is a leading cause of cancer-related death in Germany and worldwide. Non-small cell lung cancer (NSCLC) comprises 80% of lung cancer diagnoses; in White patients, around 10% of NSCLC cases are epidermal growth factor receptor mutation-positive ( EGFR m+). Head-to-head clinical trials have demonstrated superior efficacy with second-/third-generation epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) versus first-generation EGFR TKIs in EGFR m+ NSCLC. Data from routine clinical practice are necessary to confirm that clinical trial findings are transferable to real-world populations. Methods: In NCT02047903, a prospective non-interventional study in Germany, patients with EGFR m+ NSCLC received first-line afatinib until disease progression or intolerable adverse events. Key objectives were progression-free survival (PFS) rate at 12 months, objective response rate (ORR) and overall survival (OS). Safety/tolerability was also assessed. Results: Of 152 patients, 106 (69.7%) were female, 20 (13.1%) patients had an uncommon EGFR mutation and 51 patients (33.6%) had brain metastases. A starting dose of <40 mg was received by 39 (25.7%) patients. Overall, the 12-month PFS rate was 50.2% while the median PFS was 12.2 months. The ORR was 74.6% and the median OS was 30.4 months. In patients with brain metastases and uncommon mutations, the median PFS was 10.5 and 10.7 months, and the ORR was 77.3% and 83.3%, respectively. Treatment effectiveness was similar in patients with a starting dose of <40 mg (median PFS: 16.4 months; ORR, 81.3%) and a starting dose of 40 mg (median PFS: 10.8 months; ORR, 72.1%). Adverse drug reactions were manageable and consistent with the known afatinib safety profile. Conclusion: The results support clinical trial data for afatinib in routine clinical practice, including in patients generally excluded from clinical trials. Outcomes were positive in patients with uncommon EGFR mutations and in those with brain metastases. Treatment benefit was also seen in patients receiving a <40 mg afatinib starting dose, supporting patient-tailored dosing.